2010
DOI: 10.1158/0008-5472.can-09-4456
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of miR-483-3p at the IGF2/483 Locus

Abstract: hsa-mir-483 is located within intron 2 of the IGF2 locus. We found that the mature microRNA (miRNA) miR-483-3p is overexpressed in 100% of Wilms’ tumors. In addition, colon, breast, and liver cancers exhibit high or even extremely high levels of miR-483-3p in ~30% of the cases. A coregulation with IGF2 mRNA was detected, although some tumors exhibited high expression of miR-483-3p without a concomitant increase of IGF2. These findings suggested that miR-483-3p could cooperate with IGF2 or act as an autonomous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(196 citation statements)
references
References 33 publications
12
177
0
7
Order By: Relevance
“…Human miR-483 is a microRNA located within intron 2 of the IGF2 locus. It has been found that mature miR-483-3p is overexpressed in malignant mesothelioma and Wilms' tumors [34,35]. In addition, the expression level of miR-483-3p is high or extremely high in many common adult human cancers, comprising 30% of cases of colon, breast and liver cancers [35].…”
Section: Discussionmentioning
confidence: 99%
“…Human miR-483 is a microRNA located within intron 2 of the IGF2 locus. It has been found that mature miR-483-3p is overexpressed in malignant mesothelioma and Wilms' tumors [34,35]. In addition, the expression level of miR-483-3p is high or extremely high in many common adult human cancers, comprising 30% of cases of colon, breast and liver cancers [35].…”
Section: Discussionmentioning
confidence: 99%
“…miR-25 and miR-32 could directly target the pro-apoptotic function of Bim, therefore suppressing apoptosis in ovarian and human myeloid leukemia cells, respectively [172,173]. In addition, miR-483-3p might target PUMA, whose enforced expression protects cells from apoptosis [174]. miR-34 decreases the expression of Bcl-2, resulting in an increase in apoptosis [175].…”
Section: Micrornas In Extrinsic and Intrinsic Apoptotic Pathwaysmentioning
confidence: 99%
“…70,71 As for the pro-survival BCL-2 family members, BCL-2 and MCL-1 appear to be the prominent targets of miRNA-mediated regulation. Both are targeted by miR-29 and miR-153, [72][73][74] and BCL-2 expression is also regulated by miR-15, miR-16, 75 miR-195 76 and the p53-inducible miR-34.…”
Section: Mcl1mentioning
confidence: 99%